Exploring a new way to generate mesopores in lignite by employing steam explosion. Issue 5 (4th March 2021) - Miao, Zhenyong; Pei, Zhen; Gao, Mingqiang; Wan, Keji; He, Qiongqiong
ABSTRACT: Currently, the material utilization of coal is attracting more attention. In this study, the steam explosion (SE) was applied to enlarge the pore structure of lignite to improve its adsorption ability. Firstly, the lignite coal was cooked by steam at the temperature of 493 K and 10 min later, the steam release was completed within 0.0875 s to form suddenly explosion, which conversed the thermal energy into mechanical energy. To fully describe the changes of pores in lignite during SE, both of MIP and BET measurement methods were applied. It shows that SE can greatly facilitate the generation of mesopores in coal, and the increasing amounts of pores in the range of 6 ~ 12 nm were quite apparent. The total volumes of mesopores in MD and SL lignite were sharply increased by 31 and 19 times, respectively. Besides, the micropores were also increased more than three times of raw coal after SE. Based on the curve-fitting of overlapped peaks in FTIR spectra, it shows that the changes in carboxyl and hydrogen bonds of lignite coal during SE were limited, and most of these polar sites can be maintained. Overall, SE has the potential to be used to prepare the coal-based adsorbent for the organic pollutants with large molecular weight.